ANALYSIS OF FINANCIAL DISTRESS BEFORE AND DURING THE COVID-19 PANDEMIC (CASE STUDY ON A REGISTERED MINING COMPANY ON THE INDONESIAN STOCK EXCHANGE) - FARADITA, LUTFI; Damayanti, Damayanti (Jurnal Kompetitif Bisnis, 2023)
This study aims to determine differences in the level of financial distress of mining companies before and during the Covid-19 pandemic. This study uses a quantitative approach to the type of associative research. This study used 29 mining companies which were obtained using a purposive sampling technique. With samples in the form of secondary data, namely financial reports published by mining companies from 2018-2021. To test the level of financial distress, the Altman Z-Score measurement tool is used with WCTA, RETA, EBITTA, MVETL, and STA indicators. Data processing was carried out using the Parametric Paired Sample T-Test and the Non-Parametric Wilcoxon Rank-Test. The results of this study show that there is no significant difference in financial distress between before and during the Covid-19 pandemic in mining companies listed on the IDX. The results of the Paired Sample T-Test and the Wilcoxon Rank-Test show that only the STA indicator has a difference between before and during the Covid-19 pandemic due to a decrease in the number of sales as a result of the Covid-19 pandemic.